Jejak Perkawinan Minangkabau dengan Tionghoa dalam Film Jangan Panggil Aku Cina dan Novel Mengurai Rindu - Rifki Kurniawan; Silvia Rosa; Yerri Satria Putra (Jurnal Elektronik WACANA ETNIK, 2018)
This article is the comparative analysis result of the film "Jangan Panggil Aku Cina" and the novel "Mengurai Rindu" through intertextual studies. The film "Jangan Panggil Aku Cina" and the novel "Mengurai Rindu" have three formulas of hypograms (1) expansion, found in conflict, character, and characterization, (2) conversion, found in the cast of Minangkabau and Chinese Ethnic figures and social status of the main character, (3 ) Modifications or changes, found in the “Mengurai Rindu” about the rejection of mamak over the future husband, and the way of the main character deals with mamak's rejection.